Implementasi Program Inovasi 15 Menit Rindu Membaca Di Kabupaten Ciamis - Chandra Bahari; Leza Lijayanto; Suci Fitriyani; Ahmad Arofiqi; Rida Nurfarida Rahmat (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2020)
In 2030-2040 Indonesia will face a demographic bonus so efforts to prepare for this mental revolution must be made to improve the quality of human resources. One way to do that is by increasing literacy culture among early childhood. This study aims to analyze the implementation of the 15-minute miss reading innovation program in Ciamis Regency and to find out the factors that hamper the implementation of the 15-minute miss reading innovation program. The method used is a descriptive analysis method with a qualitative approach. Where data collection through observation, interviews and documentation. The results of this study indicate that the 15-minute miss reading innovation program has the support of the local government with the issuance of the Regent's Decree as the basis for the running of this program, lack of coordination and human resources that have become a hindering factor for this program so that it has not run optimally, therefore the strategy undertaken is to carry out socialization about the importance of implementing an innovative 15-minute miss reading program for school children to create an independent, productive and quality young generation in facing the challenges of demographic bonus in Indonesia.